Physical rehabilitation based on kinect serious games - Ferreira, D. (2018)
This article presents a serious game framework developed using Unity 3D game engine and Kinect V2 sensor as a natural user interface. The developed serious games are used for objective evaluation of physical rehabilitation considering the Kinect V2 sensors for 3D motion detection of different body joints training and provide different types of data, such as angles velocities, for physiotherapists and patients during the rehabilitation process. The framework provide data storage capability in a remote database thus patient's biometric data, patients' medical record, obtained scores during serious game based training and values of metrics such as the distance between feet during game, left right feet usage frequency and execution time for imposed movement associated with game mechanics. A general description of the applied technologies on serious game for lower limb rehabilitation developments as so as the experimental results obtained for a set of volunteers are included in the paper.